Efficacy and safety of dexmedetomidine in peripheral nerve blocks: A meta-analysis and trial sequential analysis. Issue 10 (October 2018) - Schnabel, Alexander; Reichl, Sylvia U.; Weibel, Stephanie; Kranke, Peter; Zahn, Peter K.; Pogatzki-Zahn, Esther M.; Meyer-Frießem, Christine H.
Abstract : BACKGROUND: The duration of analgesia provided by nerve blocks is limited if local anaesthetics are administered alone. Therefore, several additives, including dexmedetomidine (DEX), have been investigated in order to prolong postoperative analgesia following single-shot regional anaesthesia. OBJECTIVES: The aim of this meta-analysis was to assess the efficacy and safety of the addition of perineural DEX to local anaesthetics compared with local anaesthetics alone or local anaesthetics combined with systemic administration of DEX. DESIGN: A systematic review of randomised controlled trials (RCT) with meta-analysis, trial sequential analysis and assessment of the quality of evidence by the GRADE approach. DATA SOURCES: The databases MEDLINE, CENTRAL and EMBASE (to May 2017) were systematically searched. ELIGIBILITY CRITERIA: All RCTs investigating the efficacy and safety of perineural DEX combined with local anaesthetics compared with local anaesthetics alone or local anaesthetics in combination with systemic DEX in peripheral nerve blocks of adults undergoing surgery were included. RESULTS: A total of 46 RCTs (3149 patients) were included. Patients receiving perineural DEX combined with local anaesthetics had a longer duration of analgesia than local anaesthetics alone [mean difference 4.87 h; 95% confidence interval (95% CI) 4.02 to 5.73; P < 0.001; I 2 = 100%; moderate-quality evidence]. The most important adverse events in the DEX group were intraoperative bradycardia [risk ratio 2.83; 95% CI 1.50 to 5.33; P = 0.035; I 2 = 40%; very low-quality evidence] and hypotension (risk ratio 3.42; 95% CI 1.24 to 9.48; P = 0.002; I 2 = 65%; very low quality evidence). In contrast, there were no differences in the duration of analgesia between perineural or intravenous DEX combined with local anaesthetics (mean difference 0.98 h; 95% CI −0.12 to 2.08; P = 0.08; I 2 = 0%). CONCLUSION: This meta-analysis demonstrated that DEX in combination with local anaesthetics increases postoperative analgesia for around 5 h. However, there are higher risks of intraoperative hypotension and bradycardia. Findings on side effects are associated with high uncertainty. Initial evidence suggests no difference in the duration of analgesia associated with systemic or perineural DEX. TRIAL REGISTRATION: CRD42016042486 Abstract : Supplemental Digital Content is available in the text